Leadership Functions in Managing a Parent Teacher Association - Ismail, Ismi Arif (1999)
This inquiry studied the nature of leadership in Parent Teacher Association (PTA) and how it functions in the management of the organisation. The study used qualitative case study as the methodology. The informants were PTA exco members, teachers and parents. Semi-structured interviews which were recorded act as the primary data of this inquiry. Each recorded interview was transcribed verbatim into the computer. There searcher has also used documents provided by informants to support the findings. Data were managed using a personal computer and the 'cut and paste' method. The study found that the PTA leadership focused more on the task related activities than the relationship activities. Teachers were found to be more actively involved than parents. The communication between parents and teachers was minimal and stunted the efforts of developing a PTA which balances between carrying out various activities and simultaneously building a close knitted relationship among members.